К понятийной типологии словосочетаний курдского языка - Хамоян, Максим («Զանգակ - 97»)
In the given research work the character of the denotatums of wordcombinations is discussed, thanks to which it’s possible to reveal the whole system of peculiar concepts of the expression forms of words combinations and also their principles of structural and semantic syntax classification.
Keywords: Лингвистика; Филология